Fertility Decision-Making Among Kenyan HIV-Serodiscordant Couples Who Recently Conceived: Implications for Safer Conception Planning - Pintye, Jillian (AIDS Patient Care STDS, 2015)
HIV-serodiscordant couples often choose to attempt pregnancy despite their HIV transmission risk. Optimizing delivery of HIV risk reduction strategies during peri-conception periods (i.e., safer conception) requires understanding how HIV-serodiscordant couples approach fertility decisions. We conducted 36 in-depth individual interviews with male and female partners of Kenyan heterosexual HIV-serodiscordant couples who recently conceived. Transcripts were analyzed by gender and HIV serostatus using open coding. Matrices were used to identify patterns and emerging themes. Most participants expressed acceptance of being in an HIV-serodiscordant couple and affirmed their resilience to live with serodiscordance and achieve their fertility goals. Overall, while the goal for childbearing was unchanged, conception became an urgent desire so that both partners could experience childrearing together while the HIV-infected partner was still healthy. Children also add value to the relationship, and multiple children were a commonly expressed desire. Couples' desires dominated those of individual partners in fertility decision-making, but male preferences were more influential when the individual desires differed. Values and preferences of the couple as a unit may mediate fertility decision-making in HIV-discordant couples. Thus, it is important that safer conception programs include both partners when appropriate and consider the relationship context during risk reduction counseling and when recommending risk reduction interventions.